A more relevant grading system for Indian pig carcasses - THOMAS, R; BANIK, S; BARMAN, K; MOHAN, N H; RAJKHOWA, S (The Indian Journal of Animal Sciences, 2018)
A good grading scheme can lead to improvements in efficiency, as producers have a financial incentive to modify their production methods to produce carcases that are the most desired by consumers. In India, consumers and producers often do not have a clear understanding of pork grading and are not into practice. The existing Indian Standard for Specification for pork, i.e. IS: 1723-1973 specifies only two grades of pork, i.e. Grade 1 and Grade 2, which is per se insufficient to meet the current marketing requirements. Thus, a more relevant pork grading system was developed with distinct yield grades (Grade 1, 2, 3 and 4 in case of gilt/barrow and Grade 1, 2, 3 and C in case of sow) and quality grades (Grade P, I, N and D). Different classes of grades for gilt/barrow and sow carcasses was necessitated due to distinct difference observed in the pattern of change among the parameters, which directly affected the carcass yield, viz. chilled carcass weight, back fat thickness and percent yield of primal cuts. Data were collected from 1,017 pigs of different breeds and varieties over a period of 9 years and critically analyzed before assigned them to the respective grades. Also, to ensue uniformity in the dressing operations of different pig carcass and to facilitate grading, standard dressing specifications were developed based on chilled carcass weight, separately for gilts/barrows and sows. The new grading system has elements of both classification and grading schemes and is simple to understand and perform.